2020
DOI: 10.1007/s00221-020-05933-5
|View full text |Cite
|
Sign up to set email alerts
|

Intensity dependent effect of cognitive training on motor cortical plasticity and cognitive performance in humans

Abstract: Intervention-induced neuroplastic changes within the motor or cognitive system have been shown in the human brain. While cognitive and motor brain areas are densely interconnected, it is unclear whether this interconnectivity allows for a shared susceptibility to neuroplastic changes. Using the preparation for a theoretical exam as training intervention that primarily engages the cognitive system, we tested the hypothesis whether neuroplasticity acts across interconnected brain areas by investigating the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The patient was prostrate on the treatment bed, and the rTMS monopulse mode stimulated the thumb motor cortex (M1) on the dominant side of the hand 10 times, at least 5 of which induced the thumb abductor muscle movement, and the stimulus intensity energy is RMT, which is a necessary step before rTMS treatment, and there are individual Mediators of Inflammation differences. The patient was placed on the treatment bed in a relaxed state, and the medtronic MagPro magnetic stimulator was used to determine the stimulation site according to the international EEG 10-20 system [22,23]. The highfrequency stimulation site was left dorsolateral prefrontal cortex, the stimulation coil was tangent to the scalp, and the coil handle was backward, the stimulation intensity was 80% motor threshold (MT), the stimulation frequency was 10 Hz, the stimulation was 4 s once, the interval was 56 s, and the stimulation of 30 sequences was a single treatment, once a day, 5 times a week, and the rest was 2 days, 4 weeks as a course of treatment, a total of 2 courses of treatment, and a total of 40 times.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…The patient was prostrate on the treatment bed, and the rTMS monopulse mode stimulated the thumb motor cortex (M1) on the dominant side of the hand 10 times, at least 5 of which induced the thumb abductor muscle movement, and the stimulus intensity energy is RMT, which is a necessary step before rTMS treatment, and there are individual Mediators of Inflammation differences. The patient was placed on the treatment bed in a relaxed state, and the medtronic MagPro magnetic stimulator was used to determine the stimulation site according to the international EEG 10-20 system [22,23]. The highfrequency stimulation site was left dorsolateral prefrontal cortex, the stimulation coil was tangent to the scalp, and the coil handle was backward, the stimulation intensity was 80% motor threshold (MT), the stimulation frequency was 10 Hz, the stimulation was 4 s once, the interval was 56 s, and the stimulation of 30 sequences was a single treatment, once a day, 5 times a week, and the rest was 2 days, 4 weeks as a course of treatment, a total of 2 courses of treatment, and a total of 40 times.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…First, changes in structural and functional synaptic plasticity, such as reduced synaptic density in dorsolateral prefrontal cortex (DLPFC), the anterior corpus callosum (ACC), and the hippocampus ( 5 , 50 , 51 ) are described in MDD, likely leading to reduced functional connectivity within and between networks underlying mood and cognition. The motor cortex is an important node in the brain and processes information from various inputs ( 52 , 53 ) as it is strongly interconnected with numerous brain areas. Several key structures of the cognitive network, such as the DLPFC ( 54 ), the posterior parietal cortex ( 55 ), as well as frontal areas ( 56 ) have been shown to be connected to the motor cortex, as several double-pulse TMS studies ( 57 60 ) as well as cortico-cortical paired associative stimulation studies have shown ( 61 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…From an evolutionary perspective, the motor act is the set of movements oriented to a purpose, while the action is a sequence of motor acts oriented to a purpose. If it is true that the purpose guides the chain of movements, it is also true that to achieve it, mental structures are needed to organize the motor system (Berns et al, 2020). Brain maturation, together with physiological and musculoskeletal development, determine the evolution of motor development.…”
Section: Discussionmentioning
confidence: 99%